The narrated social and sexual experiences of black gay university students who have sex in the closet - Kekana, Putuke (My University, 2017)
The aim of this study was to enquire on the narratives of black gay South African university students who are ‘in the closet" i.e. their parents do not know about their sexuality only a few trusted friends within the university space. These narratives focused on their social and sexual experiences which involved their interactions within the university as black gay men in the closet. Four black gay students from two Johannesburg universities aged 21 to 24 participated in this study. The study made use of a qualitative research design grounded in Narrative Theory. Unstructured interviews were conducted and the collected narratives were analysed using Narrative Analysis. Each participant narrated different individual experiences of the university space as well as how they negotiated their sexual practices as gay men who are in the closet. The participants offered knowledge about the university spaces that they occupied as well as the communities in which they were raised. The participants" narratives highlight the intersectional challenges black gay men from township and rural South Africa endure because of social constructs of heteronormativity, hegemonic masculinity, religious intolerance and homophobia, all which were perpetuated within these spaces. These challenges also affected their sexual experiences; influencing their lack of interest in sexual intercourse. The study highlights the importance of creating safe spaces for gay people to express their sexuality visibly. The study argues that visibility can challenge social ills experienced by gay people within university spaces and the country at large.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree Master of Arts in Social & Psychological Research 2017.
Keywords: Educational change--South Africa; Gay rights; Educational equalization--South Africa